A rare solid variant of primary neuroendocrine carcinoma of breast - Panjvani, Sahil I; Gandhi, Minesh B; Chaudhari, Bhawana R; Sarvaiya, Ankur N (Annals of Pathology and Laboratory Medicine, 2015)
Solid Primary Neuroendocrine Carcinoma of Breast (NECB) is an extremely rare tumor of breast. Much less is known about it because of only few reported cases. Immunohistochemical examination showing expression of chromogranin and/or synoptophysin in more than 50% of cell population confirms evidence of neuroendocrine carcinoma. Here, we describe a case of 70-years old patient with brief review of clinopathological features, treatment and prognosis of solid NECB. Microscopy Solid islands of tumor cells are separated by fibrovascular stroma. Tumor cells are round to oval, polygonal with finely granular (stippled) nuclear chromatin with eosinophilic cytoplasm and immunohistochemistry reveal strong and cytoplasmic positivity for synaptophysin inÂ  >50% tumor cell population.Â 